Analysis of Marketing Strategy of Freshwater Ornamental Fish Business in Bandung City, West Java Province - Haganta, Louise David; Nurhayati, Atikah; Liviawaty, Evi; Gumilar, Iwang (Sam Ratulangi University, 2024)
The purpose of this study is to analyze appropriate marketing strategies that can be applied to the freshwater ornamental fish business in Bandung City. The research will be conducted in a time frame and location from March to April 2024 in Bandung City. The analysis method used is SWOT analysis. The initial stage involves the analysis of internal factors (IFAS) and external factors (EFAS). Next, perform the calculation of the IFE EFE matrix and the formulation of marketing strategies using the grand strategy matrix. Based on the results of the analysis, both internal factors and external factors each have 5 factors. Strengths include Good quality ornamental fish, strategic location, affordable prices, a large selection of fish species, and comfortable and clean stores. Weaknesses include hampered marketing activities, promotion has not been maximized, fish dying from the disease, do not update on social media, and unsatisfactory service. Opportunities include the trend of ornamental fish, the number of ornamental fish suppliers being relatively large, supportive government policies, consumer confidence in products, and ornamental fish as a hobby or decoration. Threats include changes in consumer tastes, increasingly fierce business competition, price games from competitors, the entry of ornamental fish from abroad, and a lack of market information. The results of the grand strategy matrix analysis show that the position of the X-axis (0.48) and the Y-axis (0.42) is in quadrant I, so the right strategy that can be applied is an aggressive strategy (SO) which means utilizing strengths and opportunities. S-O strategies that can be applied include maintaining and improving the quality of ornamental fish, increasing the number of different types of ornamental fish, setting prices that can be reached by consumers, expanding ornamental fish business premises, and arranging and maintaining the cleanliness of business premises. Keywords: SWOT analysis; Freshwater ornamental fish; Marketing strategy. Abstrak Tujuan penelitian ini adalah untuk menganalisis strategi pemasaran yang tepat yang dapat diterapkan pada usaha ikan hias air tawar di Kota Bandung. Waktu dan lokasi penelitian dilakukan pada bulan Maret sampai bulan April 2024 di Kota Bandung. Analisis yang digunakan dalam penelitian ini adalah analisis SWOT. Tahap pertama dengan melakukan analisis faktor internal (IFAS) dan faktor eksternal (EFAS). Berikutnya melakukan perhitungan matriks IFE EFE dan perumusan strategi pemasaran menggunakan matriks grand strategi. Berdasarkan hasil analisis faktor internal dan faktor eksternal masing-masing memiliki 5 faktor. Kekuatan meliputi Kualitas ikan hias baik, lokasi strategis, harga yang terjangkau, banyak pilihan jenis ikan, dan toko yang nyaman dan bersih. Kelemahan meliputi Kegiatan pemasaran terhambat, promosi belum maksimal, ikan mati karena penyakit, tidak update dimedia sosial, pelayanan yang tidak memuaskan. Peluang meliputi Tren ikan hias mengalami peningkatan, jumlah pemasok ikan hias relatif banyak, kebijakan pemerintah yang mendukung, kepercayaan konsumen terhadap produk, dan ikan hias sebagai hobi ataupun hiasan. Ancaman meliputi perubahan selera konsumen, persaingan bisnis semakin ketat, permainan harga dari pesaing, masuknya ikan hias dari luar negeri, dan kurangnya informasi pasar. Hasil dari analisis matriks grand strategi menunjukkan posisi sumbu X (0,48) dan sumbu Y (0,42) berada pada kuadran I, maka strategi yang tepat yang dapat diterapkan adalah strategi agresif (SO) yang berarti memanfaatkan kekuatan (strength) dan peluang (opportunities). Strategi SO yang dapat diterapkan antara lain Mempertahankan dan meningkatkan kualitas ikan hias, menambah jumlah jenis ikan hias yang berbeda, menetapkan harga yang dapat dijangkau oleh konsumen, memperluas tempat usaha ikan hias, serta menata dan menjaga kebersihan tempat usaha. Kata Kunci: Analisis SWOT; Ikan hias air tawar; Strategi pemasaran.